SOIL REINFORCEMENT WITH COMBINATION ROOTS SYSTEM: A CASE STUDY OF VETIVER GRASS AND ACACIA MANGIUM WILLD - P. Voottipruex; D. T. Bergado; W. Mairaeng; S. Chucheepsakul; C. Modmoltin (Lowland Technology International, 2008)
This paper focussed on the effect of combination root reinforcement system on soil slope stability. Consequently, an attempt was made to study the effect of Vetiver grass roots in combination with Acacia Mangium Willd roots on shear strength of soil. To assess the mechanisms of root anchorage and root reinforcement within two years growth period, the plants were pulled out to determine their pullout resistance as well as their penetration into the soil. In addition, large scale field direct shear tests were carried out on both rootless and root reinforced soil. A composite soil-root system was developed to evaluate the contribution of combination root reinforcement to shear strength. Subsequently, the results revealed that there are significant root reinforcement effects of 1.5 times increase by Vetiver grass and 3.0 times increase by Acacia tree in the soil shear strength root reinforcement in the slope stabilization scheme. Consequently, this paper proposed the critical zone and selected soil moisture content to calculate the strength increment of the combination root reinforcement soil system for successful slope stabilization.